Technical electricity and electronics - Buban, Peter; Schmitt, Marshall Langdon, 1919- (New York : McGraw-Hill, 1977)
An advanced electronics textbook for students in senior high school, industrial education, and vocational education.
Includes index.
Keywords: Electrical engineering; Electronics; Electrical engineering; Electronics